FARMASEVTIKA MAHSULOTLARI BOZORIDA KOMPANIYANING MIJOZLAR BILAN MUNOSABATLARINI OʻZIGA XOS XUSUSIYATLARI (Marketing Jurnali, 2025)
In todayʼs highly competitive pharmaceutical market, building and maintaining strong customer relationships is more important than ever. With rapidly evolving pharmaceutical product needs and increasing demand for personalized services, pharmaceutical comp anies must go beyond simply delivering products – they must foster trust, loyalty, and open communication with their customers. Whether a manufacturer, distributor, or healthcare provider, understanding the challenges and 327 opportunities in this industry is key to developing meaningful relationships that lead to long-term success. This article outlines the specifics of building customer relationships in the pharmaceutical market, which will help create long -term partnerships that benefit the business.
Keywords: mijozlar bilan aloqalarni boshqarish; xarajatlar nazorati; rentabellik; patent muhofazasi